La stampa a Perugia nel Rinascimento Dai tipografi tedeschi agli editori locali - Panzanelli, Alessandra (Studi e ricerche di storia dell'editoria, 2020)
The art of printing with movable type made its appearance in Perugia -then as now, the heart of Italy- in 1471, when the city was under the sway of Braccio Baglioni. Perugia was home to an important university which had been attracting students from all over Europe for more than a century. They found hospitality in two colleges, of which the 'Sapienza Vecchia', in particular, was accustomed to accommodating students from abroad. The colleges were themselves instrumental in assisting the work of the earliest printers, all of them foreigners; their enterprise flourished for about fifteen years before strong competition from larger printing centres, notably Venice, took control of the Perugian book market. A second phase in local book production started at the turn of the century under the aegis of two major players, the Cartolari family and Bianchino dal Leone. The history of the book in Perugia is characterized by a quality and originality which is not reflected in the modest quantities produced there, and the major bibliographers have always taken an interest in it. All that and more can be found in this book, the outcome of lengthy research based on detailed analysis of all known editions and archival documents, including a number of new discoveries.